Kinematic and kinetic variability associated with the cable put and seated rotation assessments. Issue 6 (18th March 2020) - Schofield, Mike; Neville, Jono; Hébert-Losier, Kim; Cronin, John B.; Uthoff, Aaron M.
ABSTRACT: When new protocols are developed, there is a requirement to investigate test–retest reliability of measures for valid use and interpretation of data in research and practice. Therefore, the aim of this investigation was to determine the inter-day reliability of the cable put and seated rotation assessment protocols. On three occasions, nine resistance-trained men performed cable puts and cable rotations at different loads between 6 and 42 kg on a commercially available cable cross over machine. Load stack movement was recorded using a PT5A linear position transducer from which all kinematic and kinetic variables were calculated. Reliability was excellent for peak velocity and displacement based on intraclass correlation coefficient (ICC) and coefficient of variation (CV) across the majority of loads and movements (cable put: ICC = 0.92 to 0.99, CV = 3.1% to 8.6%; cable seated rotation: ICC = 0.76 to 0.99, CV = −1.7% to 16.1%). However, kinetic variables demonstrated inadequate reliability across the majority of days, loads and movements (ICC = 0.70, CV >10%). It was concluded that peak velocity is a reliable kinematic measure to assess muscular capability from cable put and seated rotation protocols; however, kinetic measures are too variable to provide reliable outputs across testing occasions.